Effect of rapid solidification and heat treatment on Co-20 wt. %Cr alloy for biomedical applications - Ramirez-Ledesma, A L; Aguilar-Mendez, M A; Rodriguez-Diaz, R A; Juarez-Islas, J A (Journal of physics. Conference series, 2015)
A series of cobalt-base alloys with different chromium contents (20, 25, 30, 35, 40 and 44 wt. %) were melted into an induction furnace with argon atmosphere and casted into a chill cooper mold. The characterization of samples was carried out with a scanning electron microscope in order to evaluate the effect of chromium additions on microstructure. The resulting microstructure consisted mainly of columnar dendrites with randomly distributed precipitates in primary and secondary dendrite arms. X-ray diffraction patterns in as-cast samples identified the presence of both ϵ-hcp and the metastable α-fcc cobalt solid solution. As the Cr-content increased, the amount of both interdendrite segregation and precipitates increased too. From the Co-Cr alloys under study, the Co-20 wt. % Cr alloy showed a microstructure nearly free of interdendrite segregation and precipitation therefore was subject to an additional heat treatment to improve elongation from 2.6%, in the as-cast condition to 25.5% in the as-heat treated condition.